Strigolactones: a new musician in the orchestra of plant hormones - Kholen, Wouter; Ruyter-Spira, Carolien; Bouwmeester, Harro J (Botany, 2011)
Strigolactones are known as germination stimulants for seeds of root parasitic plants of the Orobanchaceae and as the presymbiotic branching factor for arbuscular mycorrhizal fungi. They were also recently identified as a new class of plant hormones and have been the subject of many studies, leading to much advancement in our knowledge of how these molecules are involved in controlling plant development. In the first place, this concerns their role in the inhibition of shoot branching, but a number of studies have also revealed a role for strigolactones in shaping root system architecture or have suggested involvement of strigolactones in seed germination, hypocotyl elongation, and reproductive development. In all these studies, the interaction of strigolactones with other plant hormones such as auxin, abscisic acid, and ethylene is becoming clear. In this review we discuss the progress over the past 5 years in our understanding of the physiological role of strigolactones in the regulation of plant development.